Teacher evaluation: a qualitative study - Shalaby, Nahed Mohammed (AUC Knowledge Fountain, 2012)
The evaluation of teacher performance is a hot topic worldwide. Evaluating a classroom teacher is one of the most debatable issues among educators, politicians, policy makers, business leaders, community activists and parents. The evaluation of the teachers can be defined as a mechanism aiming to enhance teachers' instructional and management practices in the classroom by using methods to judge their performance based on specific standards that will be reflected on their promotion and job retention. In general terms, teachers are mainly evaluated on the basis of their classroom management, instructional abilities, selection of classroom resources, knowledge of subject, communication skills, professional behaviors, students' skills acquisition, organizational skills, and personal attributes.